2011
DOI: 10.1590/s0100-29452011005000050
|View full text |Cite
|
Sign up to set email alerts
|

In vitro organogenesis in some citrus species

Abstract: ABSTRACT-In vitro organogenesis of citrus was studied for the genotypes Citrus sinensis cv. 'Natal', C. limonia, C. volkameriana, and C. aurantium, with the use of epicotyl segments-derived explants, cultured in MT salts and vitamins medium supplemented with different concentrations of 6-benzylaminopurine (BAP -0.0; 0.5; 1.0; 1.5, or 2.0 mg L -1 ). For the recalcitrant genotypes C. limonia and C. aurantium the in vitro organogenesis was also studied with internodal segments-derived explants, cultured in MT sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(16 reference statements)
1
3
0
1
Order By: Relevance
“…The highest number of shoots were obtained in 1.5 mg/l BAP, 0.5 mg/l BAP + 1 mg/l Kn and 0.5 mg/l Kn + 1 mg/l BAP + 1 mg/l 2,4-D. Similar result was reported in Citrus volkameriana (Schinor et al 2011) where the number of shoots increased when 1.5 mg/l BAP was used. The multiplication of shoots appeared to be affected by the use of BAP.…”
Section: Resultssupporting
confidence: 84%
“…The highest number of shoots were obtained in 1.5 mg/l BAP, 0.5 mg/l BAP + 1 mg/l Kn and 0.5 mg/l Kn + 1 mg/l BAP + 1 mg/l 2,4-D. Similar result was reported in Citrus volkameriana (Schinor et al 2011) where the number of shoots increased when 1.5 mg/l BAP was used. The multiplication of shoots appeared to be affected by the use of BAP.…”
Section: Resultssupporting
confidence: 84%
“…The results of the table showed the significant effect of the triple interference of the experimental factors in the characteristic of plant height, as the interference treatment the rootstock of Volkameriana and coconut liquid 200 g L -1 and yeast extract at a concentration of 8 g L -1 achieved the highest rate of 37.863 g compared to the interference treatment of the rootstock of Citrus aurantium and coconut liquid 0 g L -1 and yeast extract 0 g L -1 as it recorded the lowest rate of 17.903g an increase of 111.489% . Tables (1,2,3,4,5,6) show the superiority of the Volkameriana rootstock over the Citrus aurantium rootstock in the studied vegetative traits, which may be due to the nature of the genetic structure of the root and may be due to the high specifications that characterize this rootstock and its positive effect on the grafts growing on it and its compatibility with most types of citrus fruits as well as its resistance to rapid deterioration disease, wood pecking, and viroid bark scaling disease [9] and [20]. Also, this root is considered the best in terms of characteristics compared to Citrus aurantium and other rootstocks, and this is consistent with what was confirmed by [21] and [22], where they confirmed that it is the best in terms of vegetative growth characteristics compared to the rootstock of Citrus aurantium.…”
Section: Dry Weight Of Vegetative Total (G)mentioning
confidence: 99%
“…The variations in the regenerative responses observed for the different rootstocks can be attributed to their particular genetic traits, so that genotype has a strong influence on the success of in vitro culture (SCHINOR et al, 2011).…”
Section: Culture Media For In Vitro Establishment Of Citrus Rootstocksmentioning
confidence: 99%